Disparaging Gender Stereotypes against Black African Women through Dangarembga’s Nervous Conditions - Khoza, Thulile; Montle, Malesela Edward; Mogoboya, Mphoto (Technium Social Sciences Journal, 2021)
This study has aimed to disparage the stereotypes against African women by virtue of their gender. Africa has its own cultural and traditional systems, which are practised by diverse tribes in the African continent. These African cultural and traditional systems appear to advocate for men than women and sometimes discriminates against the latter as reflected in Tsitsi Dangarembga’s Nervous Conditions. This qualitative study will use the above-mentioned novel to explore an evocation of women oppression, traditional masculinity and cultural norms in Africa. It has relied on the theory of feminism to unmask the gender stereotypes that African women endure due to patriarchal systems. Furthermore, the study finds that the African cultural and traditional systems were aided by the colonial past to subject women to stereotypical conditions.